Domače zdravljenje na Radišah - Žbontar, Damjana (Etnolog. Nova vrsta (Ljubljana), 2000)
The article focuses on home treatment or primary medicine and home care of patients at home in Radiše in Carinthia (Austria) from the end of the Second World War until 1997.
Keywords: ethnology; etnologija; Slovenci; Slovenes; Carinthian Slovenes; koroški Slovenci; ljudska medicina; zdravilstvo; nega bolnika